Effect of Repeated Thermal Shock on Mechanical Properties of ZrB2-SiC-BN Ceramic Composites - Gang Li; Hongbo Chen (The Scientific World Journal)
ZrB2-20 vol.% SiC-10 vol.% h-BN (particles) ceramic composites (ZSB) were fabricated by hot pressing under inert gas protected. ZSB samples with mean size 75 × 55 × 40 mm3 were heated using current heating method and then cooled down to low temperature by circulating water. ZSB samples repeatedly went through thermal shock with 10–50 times under various conditions, respectively. Diverse effects on residual strength of ZSB at different experiment conditions (temperatures, thermal shock times, and heating rates) were investigated. The test results indicated that the residual strength of specimen materials all reached the maximum while the temperature was 1600°C and thermal shock number was less than 50 times. Because ZSB samples could not stand the extremely serious hyperoxidation at very high temperature (1800°C), the residual strength of samples decreased sharply. At 1600°C, when the thermal shock times was 20, ZSB samples’ residual strength reached the maximum, but it decreased to the lowest point while the thermal shock times was 30. So we argued that the sensitive thermal shock number was 30. Finally, we analyzed the influences on samples residual strength generated by different heating rates at the same temperature and thermal shock number; the results showed that when heating rate was equal to cooling rate, the residual strength of specimen materials reached the maximum.